The works of John Wesley / vol. 12 Doctrinal and controversial treatises : 1 / ed. by Randy L. Maddox - Wesley, John (The works of John Wesley, 2012)
v.1 Doctrine of salvation, faith, and good works (1738), An extract of Mr. Richard Baxter's aphorisms of justificaiton (1745), An extract from the Shorter Catechism of the westminster Assembly (1753), Doctrine of original sin: according to scripture, reason, and experience (1757)